Case report: Metagenomics next-generation sequencing in the diagnosis of septic shock due to Fusobacterium necrophorum in a 6-year-old child - Zhang, Haiyang; Liu, Zhongqiang; Guan, Yuanlin; Li, Deyuan; Liu, Hanmin; Ruan, Lingying (Frontiers in Cellular and Infection Microbiology, 2024)
Fusobacterium necrophorum (F. necrophorum) infection is rare in pediatrics. In addition, the detection time of F. necrophorum by blood culture is long, and the positive rate is low. Infection with F. necrophorum bacilli usually follows rapid disease progression, resulting in high mortality. In previous reports of F. necrophorum-related cases, the most dangerous moment of the disease occurred after the appearance of Lemierre's syndrome. We report an atypical case of a 6-year-old female patient who developed septic shock within 24 hours of admission due to F. necrophorum infection in the absence of Lemierre's syndrome. F. necrophorum was identified in a blood sample by metagenomics next-generation sequencing (mNGS) but not by standard blood culture. The patient was finally cured and discharged after receiving timely and effective targeted anti-infection treatment.In the present case study, it was observed that the heightened virulence and invasiveness of F. necrophorum contribute significantly to its role as a primary pathogen in pediatric septic shock. This can precipitate hemodynamic instability and multiple organ failure, even in the absence of Lemierre's syndrome. The use of mNGS can deeply and rapidly identify infectious pathogens, guide the use of targeted antibiotics, and greatly improve the survival rate of patients. However, in recent years, there have been a few reports that F. necrophorum can transform into community-acquired invasive bacteria, leading to serious infections. It can cause either localized abscesses and throat infections or systemic, life-threatening disease [1] . Lemierre's syndrome is a rare but potentially fatal complication caused by infection with F. necrophorum, which can be defined as bacteremia, internal jugular vein (IJV) thrombophlebitis, and metastatic septic emboli secondary to acute pharyngeal infections [2,3] . The annual incidence rate of Lemierre's syndrome is relatively low, 字体: 倾斜 设置格式[Z]: N 删除[Z]:In this case, we found that due to the high virulence and invasiveness of the bacteria, F. necrophorum infection may directly cause septic shock in pediatric patients, leading to hemodynamic failure and multiorgan failure without waiting for Lemierre's syndrome.